Polymer Nanoparticles for Nanomedicines A Guide for their Design, Preparation and Development - Vauthier, Christine; Ponchel, Gilles (Springer International Publishing : Imprint: Springer, 2016)
Nanomedicines comprise a wide range of nanotechnologies including various types of nanoparticles developed as therapeutic, diagnostic and theranostic agents. The translation of nanoparticles in the clinical setting is rapidly progressing. It is now a quite well-established idea that the ultimate in vivo efficacy of nanoparticles is closely related to their characteristics. However, defining specification and designing nanoparticles based on scientifically sound justifications remains an obstacle. Another hurdle concerns the production of the nanoparticles in the requirements of clinical batch manufacturing and quality control. In these challenges, polymer nanoparticles are unique. Their characteristics can be finely tuned during synthesis and post-synthesis to cover the broad range of specificity that can be defined, with a high level of precision needed to make their in vivo application successful. Their methods of synthesis can be quite precise and most of them are scalable. The topic of the present book covers all steps of the development of polymer nanoparticles to be used as therapeutic or diagnostic nanomedicine. It is aimed to guide researchers, entrepreneurs, engineers, postdoctoral and Ph.D. students in their decisions for the design and development of nanomedicines occurring as polymer nanoparticles. The book is divided into four sections. The first and second parts describe experimental protocols as well as the methods of manufacturing and the methods of characterization that were specifically developed to be applied during the development of polymer-based nanomedicines. The third section includes a series of chapters that discusses the different topics that are accounted for while designing polymer-based nanomedicines to give them suitable characteristics. It covers the synthesis of polymers; the principles used to associate drugs and to achieve both drug loading and controlled release; the approaches developed to control interactions of the nanoparticles with proteins while they are in biological fluids and to control the in vivo fate of the nanoparticles; nanotoxicological aspects including the design of nanotheranostics with therapeutic and diagnostic tools in the same nanoparticles. The last section of the book gives prospective views on the development of this type of nanomedicines, considering their registration and potential market. This comprehensive book is fit for a wide audience, written by prominent researchers and top experts in the field of nanomedicines who share a web of established knowledge, point out unanswered questions, and discuss the field's bottlenecks in order to succeed in the development of nanomedicines made of polymer nanoparticles and to translate these into the clinic. The panel of authors reflects the different disciplines that cover the whole process of research and development of a polymer nanomedicine. Researchers and other field-related professionals can refer to the book from the early stages of the conception of a new nanomedicine to the later stages of development, including the preparation of registration, which needs to be started as early as possible, taking in mind that all choices will need to be justified. Developers will also find resources in this book to apply quality-by-design approaches when designing and developing polymer-based nanomedicines. Finally, we believe that this book, which aims to give a thorough picture of the state-of-the-art in the field of polymeric nanoparticles, will become a favorite book for anyone interested in the development of these nanomedicines. .